KONTRIBUSI STATUS SOSIAL EKONOMI KELUARGA DAN SIKAP KEBANGSAAN TERHADAP PRESTASI BELAJAR SEJARAH - Soepardjo, Soepardjo (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2013)
Penelitian ini bertujuan untuk mengetahui kontribusi 1) status sosial ekonomi keluarga terhadap prestasi belajar sejarah; 2) sikap kebangsaan siswa terhadap prestasi belajar sejarah; dan 3) status sosial ekonomi keluarga dan sikap kebangsaan secara bersama-sama terhadap prestasi belajar sejarah. Metode penelitian yang di-gunakan adalah metode survei dengan desain korelasional. Populasi penelitian 980 siswa. Sampel penelitian 245 siswa yang di-ambil dengan teknik random sampling. Pengumpulan data mengguna-kan tes dan kuesioner. Teknik analisis data menggunakan teknik korelasi dan regresi. Hasil penelitian menunjukkan bahwa 1) kontribusi positif dan signifikan status sosial ekonomi keluarga ter-hadap prestasi belajar sejarah; 2) kontribusi positif dan signifikan sikap kebangsaan terhadap prestasi belajar sejarah; 3) kontribusi positif dan signifikan status sosial ekonomi keluarga dan sikap kebangsaan terhadap prestasi belajar sejarah pada siswa SMU Muhammadiyah Kota Surakarta.Kata kunci: status sosial ekonomi, sikap kebangsaan, prestasi belajar sejarah______________________________________________________________CONTRIBUTION OF FAMILY'S SOCIO-ECONOMIC STATUS AND NATIONALISM ATTITUDE TOWARD HISTORY LEARNING ACHIEVEMENT Abstract The study aims to determine: 1) family socioeconomic status on history learning achievement; 2) nationalism attitude toward students' history learning achievement; and 3) family socio-economic status and nationalism attitude together towards achievement history. The research method used was a survey method with a correlational design. The study population was 980 students. 245 students sample were taken with random sampling technique. Data were collectied by using tests and questionnaires. The technique of data analysis used correlation and regression techniques. The results show that contribution of family socioeconomic status on history learning achievement was 9,02%. Contributions of nationalism attitudes toward achievement in learning history was 5.59% and the contribution of family socioeconomic status and attitudes nationalities together towards achievement history was 2.13%. From the result it can be concluded that there is a significant and positive contribution of 1) socio-economic status of the family; 2) nationalism attitudes; and3) socio-economic status of the family and national attitudes toward students learning history achievement at SMU Muhammadiyah Surakarta.Keywords: socioeconomic status, nationalitism attitude, history learning achievement